A Combined Approach to the Inference of Conditional Factor Models - LI, Yan (Institutional Knowledge at Singapore Management University, 2014)
This paper develops a new methodology for estimating and testing conditional factor models in finance. We propose a two-stage procedure that naturally unifies the two existing approaches in the finance literature -- the parametric approach and the nonparametric approach. Our combined approach possesses important advantages over both methods. Using our two-stage combined estimator, we derive new test statistics for investigating key hypotheses in the context of conditional factor models. Our tests can be performed on a single asset or jointly across multiple assets. We further propose a novel test to directly check whether the parametric model used in our first stage is correctly specified. In our empirical analysis, we use our new method to examine the performance of the conditional CAPM, which has generated controversial results in the recent asset-pricing literature.